ANALISIS PENGARUH ORIENTASI BELANJA DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI - Sabda Dian Nurani Siahaan; Haryani Pratiwi Sitompul (JEBIM Prima, 2021)
The development of Information, Communication and Technology (ICT) is currently being welcomed by the Indonesian through the growing development of digital businesses. The increasing of digital businesses nowadays must be followed by a business competition strategy, example: online shops. Therefore an analysis of the factors that impact the consumer buying interest in online shopping was needed. Thus this study aims to determine the effect of Shopping Orientation and Consumer Confidence on Consumer Buying Interest. The method used in this research is quantitative research methods. The population in this study were students of the Department of Economics, Faculty of Economics, Universitas Negeri Medan and the sample used was 205 people by using purposive sampling technique. The data collection technique was using a questionnaire and the data analysis method was multiple linear regression analysis. Based on the research results, it is found that (1) Shopping Orientation has a positive and significant effect on Buying Interest, (2) Consumer Trust has a positive and significant effect on Buying Interest and (3) Shopping Orientation and Consumer Trust simultaneously have a positive and significant effect on Buying Interest.